Metacognitive Strategies for Overcoming Paraphrasing Challenges in EFL Students’ Thesis Writing - Safitri, Okta Indah; Syamsiah, Nur; Misbah, Hasanul (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2026)
Paraphrasing is a key ability in academic writing. It shows that students can understand, interpret, and reiterate information while still being honest in their work. In contrast, many students learning English as a foreign language still struggle with paraphrasing, which is often owing to weak language skills and the absence of appropriate learning methods. This study explores how English Education students at UIN Raden Intan Lampung use metacognitive methods, such as planning, monitoring, and evaluation, to overcome difficulties with paraphrase in their thesis writing. Using a descriptive qualitative approach, data were obtained using close-ended questionnaires and semi-structured interviews with students in their last year of study. The thematic analysis shows that students who prepare carefully, check their understanding and how well they express themselves, and assess the quality and originality of their paraphrased work likely to create reformulations that are both cohesive and free from plagiarism. The findings indicate the necessity of developing metacognitive awareness to encourage learner independence and improve paraphrasing skills in English as a Foreign Language (EFL) academic writing.